Eastern Caribbean Regional Security System as a model for United Nations' action in relation to the security of small states - Lewis, R.E.C. (s.n. S.l., 1991)
Outlines the role of the Eastern Caribbean Regional Security System. Examines its position in relaiton to intervention and collective security in order to deduce whether similar organizations might be established under the aegis of the United Nations in other regions of the world.